Model Pintu Air Di Daerah Pasang Surut Untuk Mengurangi Intrusi Air Laut - Herdianto, Dwi Ori; Siswanto, Siswanto; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Rainfed located in coastal areas needs floodgates that serves as seawater intrusion barrier, a permanent construction has been built on desa Bantan, Kab. Bengkalis to model floodgates in form of combination of holes and threshold that function in such way. With the scientific research that has been conducted, parameters of the building which is regarded as a breakthrough can be determined. Other than that, in order to obtained the flow profile this research also yields the coefficient of discharge (Cd), correlation of discharge coefficient and height different (ΔH) and the correlation between discharge coefficient and discharge. Which is shown in the form of a logarithmic equation. With a range of discharge 101.44 cm3 / s ~ 524.89 cm3 / s , the obtained values of Cd range 0.191 ~ 0.464 cm 3 / s , and the shape of a logarithmic equation ΔH relation to the variation of Cd and Cd = 1 is 0.088 ln ( ΔH ) - 0 , 3 , while the logarithmic equation and Q is therelationship Cd Cd = 0.1212 ln ( Q ) - 0,311.Key Word :Rainfed, floodgates, hole and threshold, discharge coefficient, logarithmic equation .